Lentiviral mediated overexpression of Insulin like Growth Factor-1 in mouse myoblast - Roudbari, Z; Nassiri, M R; Tahmoorespur, M; Haddad-Mashadrizeh, A (Cellular and Molecular Biology, 2016)
Insulin-like growth factor gene (IGF-1) is one of the most important growth factors that plays a key role in the proliferation and differentiation of muscle cells. IGF-1 is also a radial stimulant in muscle hypertrophy in mammals. In our study, we constructed a lentiviral vector inducing an overexpression of IGF-1 in order to study the regulating mechanisms of this gene. The IGF-1 gene was cloned into the lentiviral shuttle plasmid pCDH-cGFP and the recombinant lentiviral vector was transducted into myoblast C2C12 cell line. The overexpression of IGF-1 was confirmed by RT-PCR and western blotting for IGF-1 receptor gene. Additionally, chemiluminescence results also showed that the concentration of IGF-1 in the transduced cells significantly increased compared to the control group. The results of our study suggests that constructed recombinant lentiviral vector can potentially be used for regulating the expression of IGF-1 in myoblast C2C12 cells.